FUMO E AGRICULTURA FAMILIAR NO CENTRO SUL DO ESTADO DO PARANÁ: CONSIDERAÇÕES A PARTIR DE UMA HISTÓRIA DAS PERCEPÇÕES - Paula, Tarcila Kuhn Alves de (2015)
The city of Palmeira is located in the South Central region of Paraná, presents itself as belonging to the core Regioal dominated and focuses most Paraná tobacco production, produced especially for family farmers. Within this reality, it is necessary to reflect on child labor, a global issue much debated in recent decades. Within the tobacco production logic, the work done by children and adolescents is often naturalized. The combination of these two factors gave rise to problems of this thesis: Understand, from a history of perceptions, what reasons lead fathers and mothers producers and tobacco producers, insert or not, your children this craft, ie as gives the understanding of child labor for this audience that in their overwhelming majority, he worked as a child in tobacco production. To achieve the objective of the research reports were used from the life story of fathers and mothers producers and producers of tobacco and also interviews with children and farmers and producers daughters